O tabaco e seus riscos para a osseointegração de implantes de titânio - Altomani, Aureo Cezar [UNESP] (2014)
Smoking is one of the major factors of failure of dental implants. Failures are related to the phases involved in the process of osseointegration and also the survival of the implants due to the increased incidence of gingivitis, peri, and as a consequence the loss of the implant. Nicotine is the drug with the highest expression in cigarettes, but many of the deleterious effects associated with this substance. The present study aims to present a review of literature on the influence of smoking on survival and bone integration of titanium implants. The literature review demonstrated that smoking is one of the risk factors for the loss of both implants prematurely as late, significantly influencing the survival of implants. Studies have also concluded that smoking increases the risk of peri-implantitis and peri-implant bone loss. However, recent systematic reviews showed no significant difference in the implants among smokers and nonsmokers failure. However, in the literature there is sufficient scientific data showing the negative effects of nicotine and smoke in the repair process in its different phases. Thus, within the limits of this study and considering the studies discussed in the literature review, we conclude that tobacco negatively influences survival and osseointegration of titanium implants